ORDINARY DIFFERENTIAL EQUATION INITIAL VALUE PROBLEM MATHEMATICAL MODELING WITH MAPLE SOFTWARE - Bauska, Renāte; Elksne, Mārīte; Kangro, Ilmārs (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2016)
Along with the rapid development of technology various problems require description and analysis of rather complicated physical processes. Due to their complexity differential equations are often used for this purpose. The aim of this work is to create mathematical models of initial value problems of ordinary differential equations using Maple software and provide insight into their practical applications. Authors have also gathered general information about differential equations and mathematical modeling. As a result two mathematical models have been created describing a process of salt dissolution in water and one-dimensional diffusion.